Improving Junior High School Students’ Reading and Writing Skills Based on Diagnostic Assessment - Purba, Mestika Pudan; Khairina, Aisyah; Manurung, Melva Adelia; Anshari, Khairil; Wuriyani, Elly Prihasti (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
This research aims to improve the reading and writing skills of SMP Negeri 1 Bahorok grade VII students by applying differentiated learning based on diagnostic assessment. The qualitative approach used in this study focuses on the student's experiences during the transition period from primary school to junior high school. This research is motivated by the variation in reading and writing skills among grade VII students, which is influenced by differences in educational backgrounds in elementary schools. Diagnostic assessments are used to identify the learning needs of each student, which further becomes the basis for designing differentiated learning. The study results show that differentiated learning improves students' reading and writing skills. Students learning according to their needs significantly improve text comprehension and writing ability. In addition, the study also found that this approach helps students adapt to the new learning environment in junior high school. This study concludes that diagnostic assessment and differentiated learning are effective strategies for overcoming Indonesian learning challenges in grade VII. This study recommends that teachers continue to develop skills in carrying out diagnostic assessments and designing differentiated learning to meet the various learning needs of students.